Analysis of the passengers' loyalty and satisfaction of Airasia passengers using classification / Ee Jian Pei ... [et al.] - Ee, Jian Pei; Chong, Pui Lin; Mohd Radzuan, Nabilah Filzah (2021)
"Business rules" of airline is to earn profits by providing air transportation services and flights to the travel passenger. Passengers purchase airline tickets base on their different requirement to choose a satisfied flight from different airlines, and become a loyal passenger to the airline due to satisfaction. The airline can establish a long-term win-win relationship with the loyal passengers which is long term purchase company's flights as the passenger can have a satisfied flight, while the airline can earn the long-term profit. This research proposes the dashboard system in finding the passengers' purchase behavior of loyalty and satisfaction from the hidden data in order to make a better business strategy in stand out from other competitors, and visualize the report. The classification method will be used included random forest, logistic regression and lightgbm. The result will identify the various possibilities of information, and contribute prediction of passenger loyalty and satisfaction.